Hazard assessment studies and multiparametric volcano monitoring developed by the Instituto Geológico, Minero y Metalúrgico in Peru - Aguilar Contreras, Rigoberto (2021)
Urban development in the areas surrounding active volcanoes has led to increasing risks in southern Peru. In order to evaluate the hazard, the Instituto Geológico, Minero y Metalúrgico (INGEMMET) created a Volcano Observatory (OVI) to carry out detailed geological investigations to understand eruption histories and provide volcanic hazard maps. The generation of geological information on volcanoes has allowed the identification of scenarios and zoning of potentially impacted areas. This information has also allowed OVI to implement surveillance networks giving priority to the volcanoes that pose the greatest risk to the population, infrastructure, and economic activities. Since 2006, OVI has been running volcanic monitoring networks with a multidisciplinary approach, improving real-time transmission, and making timely forecasts. Based on geological information and the risk posed by the volcanoes, the greatest efforts have been made to monitor Sabancaya, Misti, Ubinas, and Ticsani volcanoes. Following the order of priorities, monitoring of Coropuna, Huaynaputina, Tutupaca and, Yucamane volcanoes has also been developed. In addition, OVI carries out routine education activities and diffusion of information that serve to manage volcanic risk in Peru.